EFFECT OF TRIS AND CITRATE - QUAIL EGG YOLK EXTENDERS ON VIABILITY OF OVINE FROZEN SEMEN IN STRAWS - Cabrera V., Próspero (2011)
The study evaluated the performance of Tris-egg yolk and Citrate-egg-yolk asextenders for freezing ram semen in straws and the integrity of sperm membrane of frozensperm at the National Semen Bank – UNALM, Lima, Peru using six ram semen donors ofthree breeds. The semen was collected in an artificial vagina, diluted with Tris – glucose– quail egg yolk (Tris) or with Citrate – glucose – egg yolk (Citrate), stored in 0.5 mlpellets, and frozen in liquid nitrogen. Thawing was done at 38 ºC for 15 seconds. Inrefrigerated semen, the Progressive Individual Motility (PIM) in diluted semen with Tris was 82.3% and with Citrate was 79.2%, and the integrity of the cytoplasmic membrane(HOST) was 78.0 ± 4.4 with Tris and 73.2 ± 5.8% with Citrate. In thawed semen, PIM was62.0 and 56.8%, and HOST was 49.8 ± 3.9 and 41.3 ± 3.8% for Tris and Citrate respectively,with significant differences between extenders, rams and processing period (p<0.01).There were significant lineal regressions (p<0.001) between PIM of refrigerated semenand HOST after thawing for both extenders. It was concluded that Tris showed betterperformance than Citrate for freezing ram semen, and the hipoosmotic swelling testallowed to show differences between extenders, rams and processing periods.